2020
DOI: 10.1088/2053-1591/ab8b16
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization and exploitation of Azadirachta indica gum for the production of drug loaded nanocarrier

Abstract: In this study, gum polysaccharide of Azadirachta indica was extracted and purified. The obtained polysaccharide was subjected to TLC chromatography, spectroscopic analysis, thermogravimetric analysis and GC-MS analysis. The polysaccharide was found to have Glucose, Idosan, Allose, Galactose, Ribose and Xylose. The polysaccharide was not having antibacterial activity but possessed good antioxidant and anticancer activity. The extracted polysaccharide was further carboxymethylated and used for the synthesis of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 29 publications
2
12
0
1
Order By: Relevance
“…The sharp endothermic peak at 229.31 °C was found in a study of Nair et al; similarly, as described by the author elsewhere, in the case of TGP a sharp exothermic peak was evolved at 350 °C that shows its crystalline nature [ 52 ]. This study is also supported by Gaur et al, in which a sharp exothermic peak was found at 350 °C, which support its crystalline nature [ 62 ]. According to study of Malviya et al, a thermogram of NG–g–Am shows a single sharp exothermic peak at 249 °C.…”
Section: Resultssupporting
confidence: 86%
“…The sharp endothermic peak at 229.31 °C was found in a study of Nair et al; similarly, as described by the author elsewhere, in the case of TGP a sharp exothermic peak was evolved at 350 °C that shows its crystalline nature [ 52 ]. This study is also supported by Gaur et al, in which a sharp exothermic peak was found at 350 °C, which support its crystalline nature [ 62 ]. According to study of Malviya et al, a thermogram of NG–g–Am shows a single sharp exothermic peak at 249 °C.…”
Section: Resultssupporting
confidence: 86%
“…However, the scavenging effect of crude polysaccharide was not significant because of the huge difference in percentage scavenging compared to ascorbic acid (standard). Similar results were obtained by Samrot et al 11 who tested on Azadirachta indica gum, in which the extracted polysaccharide had scavenging activity significantly lower than the control. In contrast to the findings of this study, purified polysaccharide of Terminalia catappa L., A. heterophylla and P. chilensis showed significant antioxidant property as their percentage scavenging was comparable to the standard.…”
Section: Antioxidant Activitysupporting
confidence: 89%
“…GC analysis confirms the presence of xylose and D-allose (RT at 12.810 and 16 respectively). Samrot et al 11 reported these In another study, Samrot et al 26 found that purified polysaccharide of A. heterophylla and P. chilensis was able to inhibit swarming motility of Bacillus sp.…”
Section: Gas Chromatography (Gc) Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…Polysaccharide-based nanoparticles and hydrogels were reported to release drugsefficiently. 8,[54][55][56][57]…”
Section: Drug Release Kineticsmentioning
confidence: 99%